2017
DOI: 10.18632/oncotarget.16918
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of long non-coding RNA SPRY4-IT1 promotes tumor cell migration and invasion in lung adenocarcinoma

Abstract: Long non-coding RNAs (lncRNAs) play important role in a variety of biological processes, and are tightly associated with tumorigenesis and cancer prognosis. However, the potential power of lncRNA signatures in predicting survival of patients with lung adenocarcinoma (LUAD) has not been investigated. Here, we identified a four-lncRNA signature (SPRY4-IT1, LINC00941,GPR158-AS1 and KCNK15-AS1) displaying prognostic values for LUAD using The Cancer Genome Atlas (TCGA) dataset. Based on the four-lncRNA signature, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 29 publications
0
27
1
Order By: Relevance
“…It was initially identified to be upregulated in melanoma . In recent years, emerging studies have demonstrated the deregulation and pathogenic roles of SPRY4‐IT1 in human cancers, including lung cancer, gastric cancer, breast cancer and colorectal cancer . In melanoma, SPRY4‐IT1 expression was predominantly localized in the cytoplasm .…”
Section: Deregulated Lncrnas In Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…It was initially identified to be upregulated in melanoma . In recent years, emerging studies have demonstrated the deregulation and pathogenic roles of SPRY4‐IT1 in human cancers, including lung cancer, gastric cancer, breast cancer and colorectal cancer . In melanoma, SPRY4‐IT1 expression was predominantly localized in the cytoplasm .…”
Section: Deregulated Lncrnas In Melanomamentioning
confidence: 99%
“…43 In recent years, emerging studies have demonstrated the deregulation and pathogenic roles of SPRY4-IT1 in human cancers, including lung cancer, gastric cancer, breast cancer and colorectal cancer. [44][45][46][47] In melanoma, SPRY4-IT1 expression was predominantly localized in the cytoplasm. 48 Knockdown of SPRY4-IT1 impeded cell proliferation and differentiation but promoted apoptosis in melanoma cells.…”
Section: Spry4-it1mentioning
confidence: 99%
“…Zhang et al found SPRY4-IT1 was significantly up-regulated in LUAD tissues (not in LSCC) and further analysis show that the LUAD patients with high SPRY4-IT1 expression exhibit significantly poorer overall survival than those patients with low SPRY4-IT1 expression [33].…”
Section: Lncrna In Lung Cancer Diagnosis and Tumor Typesmentioning
confidence: 98%
“…This lncRNA was originally reported to be highly upregulated in melanoma where it played an oncogenic role . Since its discovery, a growing number of studies have reported the aberrant expression of SPRY4‐IT1 in other cancer types, such as lung, breast, gastric, oesophageal and prostate cancers . In this review, we examine current evidence on the deregulation and function of SPRY4‐IT1 in human cancers (Table and Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…17 Since its discovery, a growing number of studies have reported the aberrant expression of SPRY4-IT1 in other cancer types, such as lung, breast, gastric, oesophageal and prostate cancers. [19][20][21][22][23] In this review, we examine current evidence on the deregulation and function of SPRY4-IT1 in human cancers IT1 expression has been shown to predict survival of cancer patients. In this review, we summarize recent evidence concerning SPRY4-IT1 deregulation and the associated mechanisms in human cancers.…”
Section: Introductionmentioning
confidence: 99%